(2((x+1) ^3 – (x+1) ^2 + (x+1)) )+3

Answers

Answer 1
Answer: ( x + 1 )^3 = x^3 + 3x^2 +3x + 1;
(x + 1 )^2 = x^2 + 2x + 1;
=> (2((x+1) ^3 – (x+1) ^2 + (x+1)) )+3 =2( x^3 + 3x^2 +3x + 1 - x^2 -2x - 1 + x + 1 ) + 3 = 2( x^3 + 2x^2 + 2x + 1 ) + 3 =
= 2x^3 +4x^2 +4x + 5.

Related Questions

This questions is breaking my head... If a gumball is randomly chosen from a bag that containsexactly 6 yellow gumballs, 5 green gumballs, and 4red gumballs, what is the probability that the gumballchosen is NOT green? Can you also write ratio for me to this question?
a thirty pound bag of coffee mixture is to be made from a type of coffee that sells for $9.20 per pound and $11.00 per pound. If the mixture is to have a price of $10.28 how much of each type is included?
Oh my gosh I don't have no idea, Please help and don't forget to show your work.
The four hand of a clock moves from 12 to 5 o'clock through how many degrees does it move?
Do the ratios 4:18 and 2:9 form a proportion?yesno

Gerald says that the most common measurements is 14 quarter inches. is he right? why or whynot

Answers

Gerald is not right because the most common unit of measurement is centimeters (cm).

diketahui tiga bilangan a, b, dan c. Rata-rata dari ketiga bilangan itu sama dengan 16. bilangan kedua ditambah 20 sama dengan jumlah bilangan-bilangan yang lainnya. bilangan ketiga sama dengan jumlah bilangan yang lain dikurangi empat. Bilangan-bilangan itu berturut-turut adalah...

Answers

See the attachment ..Hope it helps

Final answer:

The question, which pertains to algebra, is asking for the solution to three equations involving three numbers. To solve the problem, we set up equations based on the information provided and then solve for the three unknowns. The solution is 10, 24, and 14.

Explanation:

This problem can be addressed using algebraic equations. We are given three unknown numbers a, b, and c. The problem provides us with the following information:

  1. The average of a, b, and c is 16, which means the sum of the three numbers is 48 (because 16 * 3 = 48).
  2. The second number, b, plus 20 equals the sum of the other two, a + c.
  3. The third number, c, equals the sum of the first two numbers minus four, or a + b - 4.

Using these equations, we can solve for a, b, and c. Our steps are:

  1. Substitute the values of a + b from the third equation into the second to get b + 20 = 2b - 4.
  2. Solve this equation to get b = 24.
  3. Substitute b = 24 into the first equation to get a + c = 24. This means a = c.
  4. Substitute a = c into the third equation to get 2a = 28, or a = c = 14.

So, the three numbers are 10, 24, and 14.

Learn more about Algebra here:

brainly.com/question/24875240

#SPJ3

Find the domain of fg. f(x)=x^2+1 g(x)= 1/x

Answers

Answer:

f(1/x)=1/x^2+1

Step-by-step explanation:

Noah rows across a river that is 48m wide. The current carries him 15m downstream. How far does Noah actually travel?

Answers

He travels 48 meters relative to the water, and 50.289 meters
relative to a person standing on the riverbank

the simple interest I (in dollars) for a savings account is jointly proportional to the product of time (in years) and the principal P (in dollars). After 11 months the interest on a principal of $3970 is $86. What is the constant of the variation

Answers

Simple interest I is jointly proportional to the product of time in years and the principal, therefore; mathematically;
I α Pt
introducing a constant;
I = kPt; but I = $ 86, P = $ 3970, while t = 11/12 years
Thus; k = I/Pt
            = 86/ 3970(11/12)
            = 0.0236
Therefore, the constant of the variation is ≈ 0.024

11Select the correct answer.
The elimination method is ideal for solving this system of equations. By which number must you multiply the second equation to eliminate the
yavariable, and what is the solution for this system?
x + 3y - 42
2x-y-14
OA. Multiply the second equation by-3. The solution is x = 12. y - 9.
ов.
Multiply the second equation by-2. The solution is x-12. y = 10.
OC.
Multiply the second equation by 2. The solution is x - 15, y = 9.
OD
Multiply the second equation by 3. The solution is x - 12. = 10.
Reset
Next

Answers

Answer:

D. Multiply the second equation by 3. The solution is x = 12, y = 10

Step-by-step explanation:

Given:

x + 3y = 42 (first equation)

2x - y = 14 (second equation)

To solve by elimination, starting with elimination of the y-variable, multiply the second equation by 3 to get a third equation.

2x - y = 14 (2nd eqn.) × 3

6x - 3y = 42 (3rd equation)

Add the 3rd equation and the 1st equation together.

x + 3y = 42 (first equation)

6x - 3y = 42 (3rd equation)

7x = 84

7x/7 = 84/7

x = 12

To find y, substitute x = 12 in the first equation

x + 3y = 42 (first equation)

12 + 3y = 42

12 + 3y - 12 = 42 - 12

3y = 30

3y/3 = 30/3

y = 10

Solution is x = 12, y = 10